Moving from eco-products to eco-services. (2001) - Bhamra, T.; Evans, S.; Zwan, F. van der; Cook, M.
This paper outlines the new approach of developing sustainable service systems. It illustrates the challenges and opportunities that arise when making the shift from eco-products to eco-services and highlights the ways in which organisations need to adapt in order to take this approach on board. A comprehensive review of existing service literature is presented and conclusions for further research established. The paper outlines two key research projects underway at Cranfield Univeristy which are focussing on moving to ecoservices and discusses the key assumptions and findings to date.